Lipopeptides in promoting signals at surface/interface of micelles: Their roles in repairing cellular and nuclear damages - Saadi, Sami; Saari, Nazamid; Mohd Ghazali, Hasanah; Mohammed, Abdulkarim Sabo; Abdul Hamid, Azizah; Nacer, Nor Elhouda; Anwar, Farooq (Elsevier BV, 2022)
Lipopeptides are recognized as a structurally diverse group of functional biopeptides. They possess multiple biological, biotechnological and therapeutic applications and are able to affect cell membrane integrity and permeability. It is widely accepted that suppressing the interaction of redooxidation is mainly aimed by inserting functional biopeptides on form alpha-helical peptides or on form antibody. Such types of structured biomaterials have great potential in promoting signal transductions to the most organelles having geometrical and spacial structures similar to endogenous liposome forms such as lysosomes, ribosomes, mitochondria and platelets.. Thus, inserting radioactive trace-elements along with biopeptides is necessary in tracing the trajectory of those radioactive micelles that are destined in targeting further complicated disease and growth factor propagation. These techniques are important in determining structure-symmetry and asymmetry leading to meso-spherical crystal-packing modes or to copolymer vesiculization. The main objective of this review is to highlight and elucidate the potential role of lipopeptides in promoting signals at surface/interface of micelles along with their functionalities in repairing cellular and nuclear damages. Moreover, state-of-the-art scientific knowledge is reviewed regarding bioconjugation and structuring charged-mono-layer and/or bi-layer phospholipidic membranes in adherent to signal-biopeptides using some advanced techniques such as ultra-sound probe based polydispersity of radioactive trace-elements assisted microdialysis as micro-separating techniques in between those miscible and immiscible compounds.